Prior Activation of 5-HT7 Receptors Modulates the Conditioned Place Preference With Methylphenidate - Carbone, Cristiana; Lo Russo, Sara Lucia Maria; Lacivita, Enza; Frank, Annika; Alleva, Enrico; Stark, Holger; Saso, Luciano; Leopoldo, Marcello; Adriani, Walter (Frontiers in Behavioral Neuroscience, 2019)
The serotonin receptor subtype 7 (5-HT7R) is clearly involved in behavioral functions such as learning/memory, mood regulation and circadian rhythms. Recent discoveries propose a physiological role for serotonin in reward-guided behavior. However, the interplay between serotonin (5-HT) and dopamine (DA) in reward-related behavioral adaptations shall be further assessed. TP-22 is a recently developed arylpiperazine-based 5-HT7R agonist showing high affinity and selectivity. Here we describe new tests with this new 5-HT7R agonist in vivo: first, in a pilot experiment assessing dosage and timing of action; then, in a conditioned place preference test with the DA-releasing psychostimulant drug methylphenidate (MPH). The pilot experiment identified the 0.25 mg/kg i.v. dosage for locomotor stimulation of rats. Acute administration of TP-22 (0.25) mg/kg 90 minutes before MPH (5 mg/kg), further increased the stimulant effect on locomotor activity. During the place conditioning test, drug-free activity of TP-22+MPH injected subjects remained steadily elevated. Finally, after a priming injection of TP-22 in MPH-free conditions, rats showed a higher preference for the MPH-associated white chamber than vehicle-primed MPH-conditioned subjects. Overall, the interaction between MPH and pre-treatment with TP-22 seems to improve both locomotor stimulation and the conditioning of motivational drives to environmental cues. Together with recent studies, a main role of 5-HT7R in processing of rewards can be suggested. In the present study, TP-22 proved to be a useful psychoactive tool to better elucidate the role of 5-HT and its interplay with DA in reward-related behavior.